H-Bridge Inverter denganBoost-up Chopper sebagai Pengondisi DayaPhotovoltaic - Suroso, Suroso (Jenderal Soedirman University, 2011)
This paper discusses anapplication of H-bridge inverter equipped with boost-up chopper circuits as photovoltaic power conditioner in stand-alone operation. First, the boost-up chopper circuits working to regulate the DCoutput voltage of photovoltaic with proportional-integral (PI) controller is described. Then, the H-bridge inverter converting the DC output voltage of chopper circuits become AC voltage waveform is presented. The uni-polar sinusoidal pulse-width modulation technique (SPWM) is appliedto the inverter circuits to produce sinusoidal output current waveform. The simulation results of the proposed photovoltaic system for different output voltages, and transient voltage wave forms are presented in the paper. The results show that the boost-up chopper circuits is effective to be appliedin the photovoltaic system to obtain stable DC output voltage of the photovoltaic, and AC voltage waveform generated bythe inverter circuits.